Tailoring the Dissolution Rate of Candesartan through Cocrystal Formation - Fatima, Dr. Zeeshan (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Cocrystal technique is a novel approach for altering the physicochemical properties of an active pharmaceutical ingredient (API). Pharmaceutical cocrystals are formed by non-covalent interactions between an API and a coformer chosen from the generally recognized as safe (GRAS) substance list. Many examples exist in the literature where the cocrystal formations have led to the improvement in the dissolution of several APIs.Aims: Candesartan is a poorly water-soluble drug having an antihypertensive effect. The objective of the research work is to enhance the dissolution rate of candesartan through cocrystallization technique. Materials and Methods: Coformers were selected from the GRAS list after identifying the hydrogen bonding groups in the drug and the coformers. The coformers employed were were nicotinic acid, succinic acid, nicotinamide, and benzoic acid. Cocrystals were prepared using solution crystallization method. The differential scanning calorimetry obtained data showed the cocrystal formation with the coformer benzoic acid only. Further characterization was carried out by thermogravimetric analysis, Fourier-transform infrared, Raman spectroscopy, and powder X-ray diffraction studies. Thereafter, the cocrystal was subjected to solubility and dissolution studies. Statistical Analysis Used: The dissolution studies were subjected to t-test using SPSS 16. Results: The analytical data confirmed the formation of cocrystal. There was 1.78-fold enhancement in the solubility and its dissolution profile also improved. Conclusions: The solubility and in vitro dissolution studies clearly demonstrated that cocrystallization of candesartan with benzoic acid may be a potential approach for improving its aqueous solubility.